Quantitative Evaluation of Nasolabial Alterations following Nasoalveolar Molding (NAM) Therapy in Patients with Unilateral Cleft Lip - Ahmed, Mairaj K.; Bui, Anthony H.; Barnett, Rebecca; Rousso, Joseph J. (Facial Plastic Surgery, 2019)
The clinical benefit of nasoalveolar molding (NAM) is actively debated between cleft centers without clear consensus. Nasolabial measurements were performed on pediatric patients with unilateral clefts of the lip, with or without cleft palate, at an academic cleft/craniofacial center prior to and following NAM therapy between June 2015 and August 2016. The parameters of interest were: columella height and width, cleft nostril height and width, and lip width. Measurements were performed using photographs taken alongside a reference object. The image output was then scaled to the size of the reference object and the capture angle. Intraclass correlation coefficient was calculated to assess reliability of the photographic measurements. Descriptive statistics (mean, standard deviation [SD]) were calculated to characterize the pre- and post-NAM measurements. Student's t-tests were performed to compare the pre-NAM versus post-NAM measurements. The primary objective was to measure the effect of NAM on the nasal aesthetic units that are known to be anatomically aberrant in the cleft lip patient. Nine patients were included in this study. Average pre-NAM age was 2.5 weeks, and average post-NAM age was 13 weeks. Average columellar height increased from 3.70 mm (SD = 0.14) pre-NAM to 5.85 mm (SD = 1.96) post-NAM (p < 0.01); average columellar width increased from 4.71 mm (SD = 0.49) to 5.93 mm (SD = 0.71) (p < 0.01); average cleft nostril height increased from 3.54 mm (SD = 2.97) to 6.81 mm (SD = 2.98) (p = 0.01); and average cleft nostril width decreased from 15.46 mm (SD = 2.91) to 11.05 mm (SD = 1.01) (p = 0.01). Average lip width decreased from 34.61 mm (SD = 1.73) to 33.87 mm (SD = 3.67); however, this change was not statistically significant (p = 0.16). This study objectively quantifies positive changes in nasal aesthetics associated with NAM therapy, providing further evidence for its utility as a presurgical treatment modality for optimal aesthetic nasal results in the unilateral cleft lip patient. The major limitation of this study was a lack of control group, as our center universally treats complete unilateral cleft lip patients with NAM therapy. However, the authors strongly believe that the positive aesthetic nasal findings would persist if compared with a non-NAM control group.
Keywords: cleft Lip; nasoalveolar molding; pediatric facial plastic surgery; cleft nasal deformity